1983
DOI: 10.1021/ic00146a021
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of metal ion coordinated imidazole and the crystal structure of pentaammine(4-nitroimidazolato)cobalt(III) chloride

Abstract: The title complex, [Co(NH3)5(N02Im)]Cl2, was prepared by the action of a standard HN03-H2S04 nitrating mixture on Co(NH3)5(ImH)3+. The complex has been characterized by NMR and UV-vis spectroscopy and a single-crystal X-ray structure determination. The pH dependence of the NMR spectra has been determined, and the pXa of the coordinated N02lm is 1.66. Crystal data for [Co(NH3)5(N02Im)]Cl2 is as follows: space group Pljn•, Z = 4; a = 9.434(2), b = 13.679 (3), c = 10.457 (3) A; 0 = 93.65 (2)°; V-1346.7 (5) A3; R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…1 and the corresponding selected bond distances (Å) and angles (°) are listed in Table 1. All of them show the cobalt atom coordinated to three iminopyrrolyl chelating ligands, in which the metal-pyrrole Co1-N1 bond distances are always shorter than the metal-imine Co1-N2 ones (see Table 1), the corresponding values being in agreement with those found for the single Co(III) aryliminopyrrolyl complex structure reported in the literature [6] and for other six-coordinated Co(III) complexes containing other anionic N-heterocyclic five-membered ring ligands [11]. All the complexes 2a-c can be described as fac (facial) isomers, since they display always the Co1-N pyrrole bonds trans to the Co1-N imine ones, likely reflecting a better stereochemical arrangement.…”
Section: X-ray Diffractionsupporting
confidence: 87%
“…1 and the corresponding selected bond distances (Å) and angles (°) are listed in Table 1. All of them show the cobalt atom coordinated to three iminopyrrolyl chelating ligands, in which the metal-pyrrole Co1-N1 bond distances are always shorter than the metal-imine Co1-N2 ones (see Table 1), the corresponding values being in agreement with those found for the single Co(III) aryliminopyrrolyl complex structure reported in the literature [6] and for other six-coordinated Co(III) complexes containing other anionic N-heterocyclic five-membered ring ligands [11]. All the complexes 2a-c can be described as fac (facial) isomers, since they display always the Co1-N pyrrole bonds trans to the Co1-N imine ones, likely reflecting a better stereochemical arrangement.…”
Section: X-ray Diffractionsupporting
confidence: 87%
“…Nitration substitution is a quite common reaction in the organic synthesis [6], while the nitration reactions through coordination are sparse. Storm and co-workers found that the nitration in HNO 3 /H 2 SO 4 in the presence of metal ions is much more rapid and milder in synthesis conditions than the reaction of free imidazole [7]. Here we present the first nitration reaction achieved only by nitrate salt rather than HNO 3 / H 2 SO 4 under hydrothermal conditions, which displays that the coordination can remarkably activate the nitration, and the hydrothermal synthesis can be widely used to construct novel architectures.…”
mentioning
confidence: 82%
“…However, the stability of the starting material in the strongly acidic H 2 SO 4 and HNO 3 solutions is impressive, attesting to the truly substitution-inert nature of Co(III) complexes. [27]…”
Section: Attempted Synthesis Of [Co(pmap)(o 2 So(oh))] 2+mentioning
confidence: 99%